Perencanaan Kawasan untuk Pengembangan Ekowisata Perairan di Teluk Weda Maluku Utara - Martini Djamhur; Boer Mennofatria; Dietriech Geoffrey Bengen; Achmad Fachrudin (Diponegoro University, 2014)
Weda Bay is a bay area which several resources likes renewable resources and unrenewable resources. This condition makes to develop Weda Bay as potential area, need zonation to arrange and make sustainable development. Water ecotourism as sustainable development is one of activity which can combine ecology and economic aspect. Based on this fact to development water ecotourism in Weda Bay, need to estimating suitablity area. Referring to Yulianda et. al (2010), suitabilty analysis for water ecotourism has done.Result showed Weda bay has suitable area for diving tourism as 488,8427 Ha; snorkeling tourism as 551,3737 Ha; beach tourism as 151,1329 Ha; mangrove tourism as 620,1251 Ha and seaweed tourism as 32,1399 Ha.Weda Bay is a bay area which several resources likes renewable resources and unrenewable resources. This condition makes to develop Weda Bay as potential area, need zonation to arrange and make sustainable development. Water ecotourism as sustainable development is one of activity which can combine ecology and economic aspect. Based on this fact to development water ecotourism in Weda Bay, need to estimating suitablity area. Referring to Yulianda et. al (2010), suitabilty analysis for water ecotourism has done.Result showed Weda bay has suitable area for diving tourism as 488,8427 Ha; snorkeling tourism as 551,3737 Ha; beach tourism as 151,1329 Ha; mangrove tourism as 620,1251 Ha and seaweed tourism as 32,1399 Ha.